A Study of Occupational Therapy Strategies and Psychological Regulation of Students’ Internet Addiction in the Mobile Social Media Environment - Xueqin Zhang (Occupational Therapy International)
This paper provides an in-depth research analysis of occupational therapy strategies and psychological regulation of students’ Internet addiction in the existing mobile social media environment. Based on the definition of Internet use peer pressure, a preliminary scale with 2 dimensions of specific behavioral pressure and psychological cognitive pressure was developed. First, a professor of mental health education and a master’s degree student in mental health education were invited to rate the scale, while 47 junior high school students were selected to try the scale to ensure that the questions of the scale were clearly expressed. Secondly, 461 subjects were selected to take the initial test of the scale, and item tests and exploratory factor analysis were conducted to ensure that the structure of the scale was as expected and the scale was expressed to psychometric standards. Finally, 810 subjects were selected for the scale retest, and item analysis and validated factor analysis were conducted, and their results met the psychometric criteria. Student peer attachment significantly and positively predicted adolescent Internet addiction; Internet use peer pressure played an incomplete mediating role in the prediction of peer attachment to Internet addiction; loneliness played a moderating role in the pathway of peer attachment to Internet addiction, and loneliness also played a moderating role in the pathway of peer attachment to Internet use peer pressure. The attitude towards online games is entertainment to kill time, a tool to escape the pressure of study and to gain the fun of friends comparing with each other. The main online motivations of adolescents included individual and situational factors, and behaviors were characterized by pan-entertainment and gamification, mainly through mobile social networks to obtain external information and knowledge, maintain interpersonal relationships, and gain a sense of belonging; they were characterized by a fixation on time, space, and online content. The interaction of family members is more of a behavioral habit, and the communication habits and behavior patterns established in the family will influence the construction of children’s relationships with others, while parents’ head-down behavior will also influence children’s attention to various needs of an Internet-dependent behavior problem, which in turn affects children’s problem-solving and intimate relationships with family members.